PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MEREK GB FASHION DI CV BUSANA INDAH KARANGANYAR - Ratri Dyah Ayu Kusumasari; Abdulah Zailani; Suharyoko Suharyoko (ITB AAS Indonesia Surakarta, 2023)
The purposes of this research were 1) To examine and measure the partial effect of product quality, perceived price and brand image on customer purchasing decisions. 2). To find out the most dominant factors influencing customer purchasing decisions 3) To test and measure the interaction of the simultaneous influence of product quality, price perception, and brand image on customer purchasing decisions. The object of this research is consumers of GB Fashion brand products at CV Busana Indah Karanganyar. The sample was taken as many as 50 respondents with random sampling method. Data analysis tools used are multiple linear regression, t test, F test, and the coefficient of determination. The results of the study found that both partially and simultaneously product quality, perceived price and brand image had a positive and significant effect on customer purchasing decisions. Of the three variables, product quality has the most dominant influence on customer purchasing decisions. Customer purchasing decisions for GB Fashion CV Busana Indah brand products are explained by product quality, perceived price and brand image variables of 82.20%. While the remaining 7.80% is explained by other factors outside this research model. Keywords: product quality, price perception, brand image, purchase decision customers, multiple linear regression.